An Empirical Analysis of Inventory Turnover Performance Within a Local Chinese Supermarket - Ali Khan, Junaid; Deng, Shiming; A.K. Khan, Muhammad Hammad (European Scientific Journal, ESJ, 2016)
Retail inventory is an important indicator for retailers as well as their shareholders and suppliers. Inventory enables retailer to sell products to customer but excessive or slow moving inventory also add extra cost. For shareholders and suppliers this is an indication of retailer’s bright or grim future. The aim of this research is to analyze the inventory turnover’s impact on the performance variables of profit margin percentage and sale surprise in one of the retailing firm of Hubei province China. We will study if inventory turnover is affected by profit margin percentage and sale surprise similarly across all categories and modes of operation in retail firm or there is some variation in the known behavior. We will be testing our hypothesis on data of a large local supermarket chain that operates in the Hubei province of China. They have multiple supermarkets in the tier 1 and tier 2 cities of the province. We investigate correlation of inventory turnover with profit margin percentage and sale surprise across different categories and modes of operation. The analysis reveals that there is a negative correlation between Inventory Turnover and profit margin percentage, while positive correlation exists between Inventory Turnover and Sale surprise across all categories and modes. But its rate of correlation varies between categories and channel structure.